Metaphor as a means of expression in postmodern architecture: Lithuanian case - Mankus, Martynas (Journal of Architecture and Urbanism, 2012)
The article tackles manifestations of metaphor seen as one of the most important instruments for creating significance and individuality in architecture; lays out the concept of metaphor in postmodern architecture which has elaborated and solidified it; and examines socio-cultural conditions of its origins. As the relation between metaphor and modernism is discussed, the intrinsic differences are identified highlighting the most pronounced stylistic features. It is implied that metaphor being transplanted to modern architecture remains an important tool for its communicative qualities. The analysis of manifestations of metaphorical aspect is based on architectural examples from Lithuania. Article in Lithuanian. Metafora kaip postmodernizmo architektūros raiškos priemonė. Lietuvos atvejis Santrauka. Straipsnyje nagrinėjamos vienos iš svarbiausių architektūros ženkliškumo ir savitumo kūrimo priemonių – metaforos – apraiškos. Analizuojama postmodernizmo architektūros, išplėtojusios ir įtvirtinusios metaforos terminą, samprata; apžvelgiamos jos atsiradimo sociokultūrinės prielaidos. Aptariant jos santykį su modernizmu, nurodomi tarpusavio skirtumai, išskiriami ryškiausi stiliaus bruožai. Charakterizuojant metaforos perkėlimą į architektūrą, daroma prielaida, kad dėl savo komunikacinių savybių ji išlieka svarbia priemone šiuolaikinėje architektūroje. Remiantis Lietuvos architektūros pavyzdžiais, nagrinėjamos metaforiškojo aspekto apraiškos. Reikšminiai žodžiai: postmodernizmas, modernizmas, metafora, forma, paviršius, Lietuvos architektūra.